ANALISIS KESELAMATAN KERJA MENGGUNAKAN METODE HAZARD IDENTIFICATION RISK ASSESMENT DENGAN PENDEKATAN SPAR-H PADA PT ARGHA PERDANA KENCANA - Isdiyati iis; Endang Suhendar; Nana Suyana (Jurnal Ilmiah Teknik Industri, 2021)
PT Argha Perdana Kencana is engaged in manufacturing molding which produces styrofoam molding tools with manual equipment and machines. The problem of PT Argha at the moment is the high level of work accidents in the machining division, so the purpose of this study is to determine the factors that cause work accidents and the application of an appropriate OHS system to minimize work accidents specifically in the machining division. The method used is the Hazard Identification Risk Assessment (HIRA) with the SPAR-H approach. By knowing the level of hazard risk effects from activities with likelihood and severity criteria and determining the level of risk (risk level) of each activity using the HIRA method, then determining the level of performance shaping factors (PSF) associated with HR and its activities. Based on the HIRA method and the SPAR-H approach, researchers can conclude that the highest occupational accidents in refinement activities are due to the high stress levels on HR at work, the high level of complexity, incomplete work procedures and an un ergonomic work environment. To solve this problem, it is advisable to procure adequate PPE according to standards, retraining workers and standardizing the work environment according to company needs.